A Ciência da Informação e o Design de Informação: perspectivas interdisciplinares - Oliveira, João Augusto Dias Barreira e [UNESP] (2015)
The development and evolution of Information and Communication Technologies (ICT) enabled the access to informational content of various types and formats on the Web promoting the urgency to discuss and address issues that permeate contemporary society related to the presentation, organization, acquisition, and dissemination of information. The problem involves the presentation and representation of information and the convergence of different languages in it. In this context, has been defined and grounded, in the form of practice, discipline and science, the term Information Design, which maintains interdisciplinary relations with Information Science. The initial epistemological research that we seek to accomplish regarding Information Design it's essential, since the issue is little explored in Information Science. We emphasize the use of the quadripolar method showing it's dynamic and advantageous for this research and possible follow ups, by outlining a consistent conceptual framework of the analyzed reality. The theoretical, exploratory and descriptive procedures made it possible to analyze the issue comprehensively. The disciplines work directly with information and are present in different informational contexts, but the ignorance of its dynamics creates lapses and flow problems in information products and services. By dealing directly with the information and communication messages we indicate the necessity to upgrade and develop visual skills by information professionals regarding the representation and presentation of textual and imagetic information with the aid of technology. The analysis of our object proved that the conditions for the practice of informational design have always existed and flourish by expanding along with technologies. It is an innovative project that has as challenge regarding acceptance and approval by the area of such foundations, principles, theories and practices applied to academic...